Investigating Inpatient Acceptance of a Unique Telemedicine Service Trialled in the Acute Ward in Rural Australia - Carol Joy Reid PhD; Catherine Church RN (Journal of Patient Experience)
This study investigated inpatient acceptance of a unique telemedicine clinical service piloted from December 2022 to June 2023 in 3 rural acute wards in Victoria, Australia. The use of virtual care was complementary to the visiting general practitioner (GP) model common in rural hospitals. The qualitative study employed 3 researcher-designed questions: Did you feel safe using the virtual healthcare doctor?; Did you feel the care you experienced was as it should be? And; If you were offered virtual care again, would you use it? Participants ( n  = 38) were predominantly over 65 years (95%). Findings describe safe care as being able to understand the virtual doctor, be listened to, and ask questions. Participants affirmed that the care experienced was helpful due to prompt in-hospital clinical interventions organized by the virtual weekend coverage. Most were first-time users of virtual care and recognized that rural doctors need a break. Barriers to acceptance of the service were concerns about the loss of in-person visits with their local doctor and that virtual care could replace local GPs.